2020
DOI: 10.1111/tmi.13369
|View full text |Cite
|
Sign up to set email alerts
|

Association between treatment with oral third‐generation cephalosporin antibiotics and mortality outcomes in Ebola virus disease: a multinational retrospective cohort study

Abstract: objective To evaluate the association between oral third-generation cephalosporin antibiotic treatment and mortality in Ebola virus disease (EVD).methods This retrospective cohort studied EVD-infected patients admitted to five Ebola Treatment Units in Sierra Leone and Liberia during 2014-15. Empiric treatment with cefixime 400 mg once daily for five days was the clinical protocol; however, due to resource variability, only a subset of patients received treatment. Data on sociodemographics, clinical characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…West Africa is endemic for this parasitic infection, and in more than 30% of the small number of patients tested there was a positive malaria diagnosis. Malaria is common and is a risk factor for death in EVD 17 and empirical antimalarial treatment may reduce case fatality. 20,21 Empiric treatment with antibiotics is frequently used as a supportive care component in the clinical management of EVD, the rationale being to mitigate the potential risk of secondary bacterial infection and gram-negative bacteraemia that arises during EVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…West Africa is endemic for this parasitic infection, and in more than 30% of the small number of patients tested there was a positive malaria diagnosis. Malaria is common and is a risk factor for death in EVD 17 and empirical antimalarial treatment may reduce case fatality. 20,21 Empiric treatment with antibiotics is frequently used as a supportive care component in the clinical management of EVD, the rationale being to mitigate the potential risk of secondary bacterial infection and gram-negative bacteraemia that arises during EVD.…”
Section: Discussionmentioning
confidence: 99%
“…7,14 Co-infection with malaria appears to be a risk factor for death. 15 Finally, there are a few studies with small numbers of patients that have found various interventions beneficial in reducing case fatality: multivitamins or vitamin A given within 48 hours of admission, 16,17 antibiotics such as thirdgeneration oral cephalosporins especially cefixime, 17 and use of empirical antimalarial treatment, especially artesunateamodiaquine rather than artemether-lumefantrine. 18,19 While existing published studies have examined risk factors for mortality, several reasons justify the need for additional research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Variable selection for inclusion in the multivariable modeling were based on identified evidence of difference (p < 0.05) in the bivariate analyses as well as on previous literature demonstrating associations with mortality in EVD. The variables included in the multivariable models, based on past literature, included: multivitamin (MVI) treatment [ 44 ], Cefixime treatment [ 45 ], clinical signs and symptoms of bleeding, diarrhea, dyspnea, and dysphagia [ 7 ], initial CT value and age [ 43 ]. Age was modeled with a cubic spline due to the previously documented quadratic relationship between age and mortality in EVD [ 43 ].…”
Section: Methodsmentioning
confidence: 99%